El Excentrico, 1976-08-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, CA; Garcia Printing, 2024)
August 5, 1976 [5 de augusto de 1976]. Ano 27, No 9. Cover contains a photo of Terry Lowry, who was the hostess of the CET Ninth Anniversary Fiesta. This event would take place at the Center For Employment Training on August 15, 1976.